Ecological indication metrics on dung beetles metacommunities in native forests and Pinus monocultures - Simões-Clivatti, Talita Rosa Otilia; Hernández, Malva Isabel Medina (Frontiers in Ecology and Evolution, 2022)
Beetles of the subfamily Scarabaeinae are commonly used as ecological indicators in studies about the effects of environmental changes. We analyzed the influence of the type of habitat, vegetation, mammals (as food resource), and temperature on dung beetle metacommunities in subtropical native forests and Pinus monocultures to evaluate the factors driving these assemblages. In the summer of 2018/2019, we sampled 12 areas in Southern Brazil, six Pinus monocultures and six native forests. We performed a dispersal test, applying a marking-recapture method. Some recaptures occurred in different habitats, showing low dispersal between habitats. We recorded behavioral activities confirming the use of both native forest and Pinus areas. The metrics did not reflect the difference in the environmental quality of the areas regarding species richness and diversity in different habitats. This shows that these metrics are not the best when using dung beetle assemblages as ecological indicators of biodiversity loss resulting from land-use changes, requiring complementing the analysis with composition analysis methods. When we partitioned beta diversity between habitats, we observed a dissimilarity between Pinus monocultures and native forest assemblages due to species substitution, with many species contributing to the dissimilarity between habitats. In our structural equation models, the influence of environmental factors on metacommunities showed no predictor related to dung beetle richness, but several variables influenced their abundance.